Employee engagement, commitment, and performance in a Malaysian GLC - Nwokolo Ebuka Paul, Sheikh Muhamad Hizam Sheikh Khairuddin, Ilham Sentosa Anwar Malik, (Opción, 2019)
The objective of the study is to examine the feasibility of the relationships between employee engagement, commitment, and performance in a Malaysian GLC via multiple techniques i.e. face validity, content validity, demographic analysis, reliability analysis (Cronbach’s Alpha), confirmatory factor analysis, and correlation analysis. The results indicated that employee engagement, employee commitment, and employee performance are positive and significantly associated at 0.01 level. Finally, correlation analysis revealed that employee engagement, commitment, and performance for the the Malaysian sample were significant and positive. In conclusion, the results from the multiple analyses conducted indicated that the study is feasible to be pursued.